2017
DOI: 10.1016/j.jpeds.2017.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-Related Gene Expression in Single Ventricle Heart Disease

Abstract: Objective To evaluate fibrosis and fibrosis-related gene expression in the myocardium of pediatric single ventricle (SV) subjects with right ventricular (RV) failure. Study design Real-time quantitative polymerase chain reaction was performed on explanted RV myocardium of pediatric SV subjects and non-failing controls. Subjects were divided into 3 groups: SV failing (SV-F, RV failure prior to or following Stage I palliation), SV non-failing (SV-NF, infants listed for primary transplant with normal RV functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Parents are carefully taught to monitor the surrogate parameters or HR and especially respiratory rate at rest; extensive monitoring of pulse oximetry at home is neither necessary nor comparably meaningful. We used the mineralocorticoid blocker spironolactone in relatively low, mainly non-diuretic dosages in approximately 80% of our patients, even though cardiac fibrosis is less pronounced in infants and small children [ 28 ]. Furthermore, we preferentially used the long-acting tissue ACEI lisinopril for additional balancing of pulmonary and systemic circulation, particularly in terms of persistence of high systemic vascular resistance following stage I.…”
Section: Discussionmentioning
confidence: 99%
“…Parents are carefully taught to monitor the surrogate parameters or HR and especially respiratory rate at rest; extensive monitoring of pulse oximetry at home is neither necessary nor comparably meaningful. We used the mineralocorticoid blocker spironolactone in relatively low, mainly non-diuretic dosages in approximately 80% of our patients, even though cardiac fibrosis is less pronounced in infants and small children [ 28 ]. Furthermore, we preferentially used the long-acting tissue ACEI lisinopril for additional balancing of pulmonary and systemic circulation, particularly in terms of persistence of high systemic vascular resistance following stage I.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibrosis has been detected in HLH by histopathology ( Kido et al, 2018 ). Increased angiotensin II and aldosterone levels promote collagen synthesis and reduce collagen breakdown by regulating matrix metalloproteinases, thereby inducing extracellular matrix (ECM) homeostasis ( Nakano et al, 2017 ). Radosinska et al (2017) found that ECM homeostasis was considered a structural and physiological foundation of the heart and that matrix metalloproteinases (MMPs) are an important environmental mediator of cardiac diastolic or systolic dysfunction ( Radosinska et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A loss of collagen fibrils is associated with LV remodelling during volume overload and with ECM remodelling in dilated cardiomyopathy [ 61 ]. Decreased collagen expression has been reported in children with failing single ventricle congenital heart disease [ 62 ]. Although, based on our current data, we cannot determine whether reduced collagen content represents adverse ECM remodelling that predisposes to cardiac dysfunction, our results clearly indicate that the exposure to maternal diabetes and Hif1a haploinsufficiency significantly affect ECM structure and composition compared with a normal myocardium.…”
Section: Discussionmentioning
confidence: 99%